Idea Kodeksu Zawodowej Etyki w Rachunkowości by Accounting Association in Poland - Żuraw, Paweł (Annales. Etyka w Życiu Gospodarczym, 2012)
Professional Ethics Code in Accounting constitutes a set of principles and values of everyday conduct of people whose work is connected with accounting. Accounting is an information system of enterprises, so it forms the basis of reliable management. Therefore information generated by accounting must be credible. Otherwise, the managing process would be based on false reports, which in consequence could lead to a fall of an economic subject, or it would at least cause the loss of clients, cooperators and associates` trust. Accounting Association in Poland as an organization with more than one hundred years` tradition for people connected with enterprise accounting out of concern for reliability and fairness of carried out and registered economic transactions, recommended the first in Poland ethics code directed to accountants as a professional group. Professional Ethics Code in Accounting is a set of norms which aim is to help people connected with accounting solve ethical dilemmas appearing in their job. It can be said that this code is, so to speak, an answer to unfair accusations formulated against accountants being (in some people`s opinion) a group of “criminals in white collars”. It is obvious that there are different people with different characters in each society. Pathologies were and will be present everywhere. Accountants` environment is not free of them, which is proved by accounting scandals in Poland and abroad (for example the case of Enron company in the United States). In order to avoid generalizing, it must be underlined that among the ones connected with accounting, there are a lot of honest people caring about the company`s good name.